ANALISIS KUALITAS SUARA PADA RUANG DENGAN PLAFOND BERBENTUK KUBAH (STUDI KASUS: AULA LANTAI 3 UNIVERSITAS ICHSAN GORONTALO) : ANALISIS KUALITAS SUARA PADA RUANG DENGAN PLAFOND BERBENTUK KUBAH (STUDI KASUS: AULA LANTAI 3 UNIVERSITAS ICHSAN GORONTALO) - Haisah, S (Program Studi Teknik Arsitektur, Fakultas Teknik - Universitas Ichsan Gorontalo, 2023)
Ceilings that function as reflectors are made with the aim of strengthening weak sound sources, but must be controlled so as not to cause echo, besides that the right ceiling design can increase sound clarity to all listeners' ears in the room. This research takes a case study on the 3rd floor of the Aulah Room at the Ichsan University Building in Gorontalo, where this room is a meeting room with a ceiling shape with variations in height differences and the use of a dome in the middle. In this study, data collection was carried out by measuring sound in the room using a Sound Level Meter and conducting simulations in the Ecotect Analysis 2011 software. The results of this study indicate that in the area around the bottom of the dome there is an increase in the sound pressure level caused by the many angles in the inner space. in the dome so that the difference in increasing the sound pressure level is higher in the first formation which reaches 23 db. This caused the whispering voices in the sitting area across from the listeners' table to become amplified and caused unexpected sound disturbance in the hall during meeting activities.